The role of prenatal diagnosis of abnormally invasive placenta in pregnancy outcome - J. Yu. Ungiadze; I. V. Nikuradze; N. D. Zamtaradze (IRBIS LLC, 2020)
Aim: to demonstrate the role and importance of prenatal diagnosis of abnormally invasive placenta.Materials and methods. Retrospective analysis of 3 clinical cases of the delivery in Health Center Medina. All women were diagnosed with the complete placenta praevia and invasion of chorion in the myometrium, the last was confirmed by the results of histological examination. Anamnesis data, extragenital pathology and results of examination during pregnancy were analyzed. In the prenatal period the diagnosis was confirmed by the results of ultrasound examination and MRI in two women.Results. All women were diagnosed with the different degree of placenta praevia, 2 women had a cesarean section in the past history. All patients had unifetal pregnancy without complications and no extragenital pathology was noted. 2 women were diagnosed with the placenta praevia using ultrasound scan and MRI, were estimated the degree and topography of placental invasion. Both women had planned caesarean section. During operation was performed autohemotransfusion using a Cell Saver system. In one of the cases urgent c-section was performed due to the massive bleeding, presence of placental invasion was diagnosed intraoperatively. Hysterectomy was performed in all 3 cases, total blood loss was 950-1450 ml in patients with the prenatally diagnosed invasive placentation. Iliac artery ligation was performed to the third patient, due to excessive bleeding and development of coagulopathy, 1200 ml of fresh frozen plasma has been transfused for correction of coagulopathy, as well as transfusion of donor erythrocyte mass.Conclusion. Probably the development of placental invasion abnormalities along with other factors is mostly affected by presence of placenta previa and cesarean section in the patient's past history. Prenatal assessment of presence and degree of the abnormal placental invasion is important factor for planning of delivery: gestational age, method and the hospital level.